PERANAN MAJALAH KAMPUS DALAM PENiNGKATAN PROSES BELAJAR MENGAJAR PADA PERGURUAN TINGGI MASA KINI DAN MASA YANG AKAN DATANG - Siswanto, Siswanto (Universitas Prof. Dr. Moestopo (Beragama), 2007)
The campus magazine is a published media by campus community,neither by ifs universitynor by student institute.Thereare some types of ifs magazine as like : The Campus News/ Popular Scientist Magazine/· Journal and Student Magazines.The campus magazine as a good potential to benefit of campus community especially to lecturer. One of the measure to know the qualityof the lecturer is the scientist writing sk,11 published in the campusmagazine.The contents of scientist writing is result of research new idea of any discipline scientific and other relevant inventions. Based on the above information the position of the campus magazine is very strategic to developing of sciences and as a barometer the success of a universityin any discipline.